Epidemiology of respiratory viral infections in children enrolled in a study of influenza vaccine effectiveness. Issue 3 (31st January 2014) - Dierig, Alexa; Heron, Leon G.; Lambert, Stephen B.; Yin, Jiehui Kevin; Leask, Julie; Chow, Maria Yui Kwan; Sloots, Theo P.; Nissen, Michael D.; Ridda, Iman; Booy, Robert
<x xml:space="preserve">Abstract</x> Background Influenza‐like illness (ILI) confers a high annual morbidity in young children. We report the epidemiology of ILIs in children who participated in an influenza vaccine effectiveness study during the 2010 Southern Hemisphere influenza season in Sydney, Australia. Methods Children aged 0·5–3 years were prospectively recruited from child care centres (CCCs). We classified them as fully vaccinated, partially vaccinated and unvaccinated according to their receipt of unadjuvanted vaccines containing influenza A (H1N1)pdm09. For 13 weeks commencing 30 July 2010, parents reported when their children developed an ILI (fever ≥37·8°C/feverishness plus ≥1 respiratory symptom) and collected nose and/or throat swabs for multiplex respiratory virus polymerase chain reaction (PCR) testing. Health impacts were assessed by telephone interview at enrolment and two weeks after each ILI. Results There were 124 ILIs reported in 105 of 381 enrolled children. Swabs were taken in 117 ILIs: 175 viruses were identified from 103 swabs. Adeno‐ and rhinoviruses were most frequently identified; 44% of swabs yielded multiple viruses. No virus was associated with more severe symptoms, although rhinovirus‐related ILIs lasted longer. Nose swabs had a higher virus detection rate than throat swabs. Influenza‐vaccinated children were 1·6 times (P = 0·001) more likely than unvaccinated children to have a non‐influenza ILI. Conclusion Adeno‐ and rhinoviruses were the most common viruses causing ILI. Swabs taken by parents are an effective method for sample collection. Influenza‐like illness was more common in children vaccinated against influenza in this observational study, but prior health‐seeking behaviour may have contributed to this difference.